Marmoset as a Model to Study Kidney Changes Associated With Aging. (13th October 2018) - Lee, Hak Joo; Gonzalez, Olga; Dick, Edward J; Donati, Andrew; Feliers, Denis; Choudhury, Goutam Ghosh; Ross, Corinna; Venkatachalam, Manjeri; Tardif, Suzette D; Kasinath, Balakuntalam S
Abstract: We evaluated whether the marmoset, a nonhuman primate, can serve as a good model to study aging-related changes in the kidney by employing healthy young and aged marmosets of both sexes. Aging was associated with glomerulosclerosis, interstitial fibrosis, and arteriolosclerosis in both sexes; correspondingly, the content of matrix proteins was increased. Functionally, aging resulted in an increase in urinary albumin and protein excretion. There was a robust correlation between markers of fibrosis and functional changes. We explored signaling pathways as potential mechanistic events. Aging in males, but not in females, was associated with reduced renal cortical activity of AMP-activated protein kinase (AMPK) and a trend toward activation of mechanistic target of rapamycin complex 1 (mTORC1); upstream of AMPK and mTORC1, Akt and IGF-1 receptor were activated. In both sexes, aging promoted kidney activation of transforming growth factor β-1 signaling pathway. While the expression of cystathionine β-synthase (CBS), an enzyme involved hydrogen sulfide (H2 S) synthesis, was reduced in both aged males and females, decreased H2 S generation was seen in only males. Our studies show that the marmoset is a valid model to study kidney aging; some of the signaling pathways involved in renal senescence differ between male and female marmosets.